„SOFT POWER” OF THE UKRAINE GEOKULTURI AND GLOBAL EDUCATIONAL INFORMATION SPACE - Костиря, І.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The Core of geo-cultural processes forms human norm and values, which forth the respective symbolic systems. Geo-cultural trends are the carriers of science and education. In the article is looked throw the fact of using the accumulated scientific and educational potential as a condition of social stability, the country's image in foreign policy and the level of national security. It is argued that the level of technology and information of education in the country depend not only on economic growth and living standards, as well as the image of state.